MENINGKATKAN KEMAMPUAN MENARI TRADISIONAL MELALUI METODE LATIHAN PADA SISWA KELAS V SDN 7 TALAGA JAYA KABUPATEN GORONTALO - Listina, Popi; Wiwy Triyanty Pulukadang; Mimy Astuty Pulukadang; La Ode Karlan; Rustam I Husain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve students’ ability to perform the Linda Dance through the drill method among fifth-grade students at SDN 7 Talaga Jaya, Gorontalo Regency. The problem addressed in this research was the low level of students’ dance performance skills, as indicated by insufficient mastery of movement techniques (wiraga), synchronization with rhythm (wirama), and emotional expression (wirasa). These limitations were attributed to less effective instructional practices and the lack of structured training activities. This research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The participants were 26 fifth-grade students, comprising 14 male students and 12 female students. Data were collected through observation, performance tests, and documentation, and were analyzed using a quantitative descriptive approach. The findings revealed a significant improvement in students’ dance performance following the implementation of the drill method. In the preliminary observation, only 27% of the students achieved the predetermined mastery criteria, while 73% failed to meet the expected standard. Following the implementation of Cycle I and Cycle II, substantial improvements were observed in the aspects of wiraga, wirama, and wirasa, as well as in students’ self-confidence and active participation during the learning process. The drill method proved effective in facilitating the gradual mastery of dance movements through systematic and repetitive practice. Therefore, it can be concluded that the drill method effectively enhances the Linda Dance performance skills of fifth-grade students at SDN 7 Talaga Jaya.